Estimates of the national trend of drugs use during 2000–2030 in China: A population-based mathematical model. (June 2019) - Su, Shu; Fairley, Christopher Kincaid; Mao, Limin; Medland, Nicholas A.; Jing, Jun; Cheng, Feng; Zhang, Lei
Abstract: Background: The use of synthetic drugs has exceeded heroin to become a major public health concern in China. We aimed to estimate the trend of heroin-only, synthetic drug-only and poly-drug (heroin and synthetic drug) use during 2000–2030 period in China using existing data. Methods: We used data from the Annual Report on Drug Control in China and peer-reviewed publications. We constructed a mathematical model to estimate the drug use trend based on Monte Carlo simulations. Results: The best calibrated model estimated that the number of drug users would increase from 0.86 million to 3, 120, 059 (95% CI 2, 669, 214-3, 570, 904) during 2000–2030 period. The proportion of heroin-only users among the total drug users will decrease from 96.8% (95% CI, 96.6–97.1%) in 2000 to 36.9% (30.1–40.8%) in 2030, while the proportion of synthetic drug-only users will increase from 1.1% (0.9–1.3%) in 2000 to 57.7% (51.7–65.6%) in 2030. In contrast, the proportion of poly-drug users shared an increasing trend during 2000–2016 (from 2.1% (1.5–2.8%) to 15.1 (13.8–17.1%)) but declined to 5.5% (3.4–7.2%) in 2030. Estimated 46, 370 (41, 634-51, 106) heroin-only users and 3767 (3481–4053) synthetic drug only users initiated poly-drug use in 2000. We observed a cross-over in 2012 where more synthetic drug-only users were initiating heroin use than heroin-only users initiating synthetic drug use. There will be estimated 2, 094, 052 (1, 819, 830–2, 368, 274) synthetic drug-only users and poly-drug users 211, 407 (177, 150–245, 664) in 2030. Conclusions: Synthetic drug use will become dominant in drug users in China, but poly-drug use of both heroin and synthetic drugs will remain substantial. Highlights: The calibrated model estimated that the number of total drug users in China would increase significantly from 2000 to 2030. Synthetic drug use will become dominant in Chinese drug users, poly-drug use will remain substantial during 2000–2030. Former heroin-only users who changed to consume synthetic drug use concurrently would dominate in poly-drug users before 2012. The results are helpful for implementing harm reduction interventions on synthetic drug use in the future.